История России: с начала XVIII в до конца XIХ в: учебное пособие / редактор А. Н. Сахаров - Сахаров А. Н. (АСТ, 1998)
Экземпляры: ЧЗ (20151028) / Инвентарный номер: 33859 / Цена: 18.15 / Сис.шифр: 63.3 / Авт.знак: И 90 / ББК: 63.3(2)